International Coordination and Support for SmallSat‐Enabled Space Weather Activities - Teresa Nieves‐Chinchilla; Bhavya Lal; Robert Robinson; Amir Caspi; David R. Jackson; Therese Moretto Jørgensen; James Spann (Space Weather)
Abstract Advances in space weather science and small satellite (SmallSat) technology have proceeded in parallel over the past two decades, but better communication and coordination are needed among the respective worldwide communities contributing to this rapid progress. We identify six areas where improved international coordination is especially desirable, including (1) orbital debris mitigation; (2) spectrum management; (3) export control regulations; (4) access to timely and low‐cost launch opportunities; (5) inclusive data policies; and (6) education. We argue the need for internationally coordinated policies and programs to promote the use of SmallSats for space weather research and forecasting while realizing maximum scientific and technical advances through the integration of these two increasingly important endeavors.